The influence of segmental and suprasegmental phonological awareness on word and pseudoword reading—A comparison between native English speakers and native Chinese speakers of English - Jiang, Ying; Gai, Xiaosong; Wang, Zhe; Thomson, Jenny (Frontiers in Psychology, 2024)
Segmental and suprasegmental phonological awareness (PA) are closely related to word reading skills in native speakers learning to read an alphabetic script as used in English. However, their roles in English word and pseudoword reading among native Chinese (NC) speakers, and how English proficiency might affect these relationships, remain less clear. This study examined the links between English segmental/suprasegmental PA and word/pseudoword reading in NC and native English (NE) speakers. Both child and adult participants were assessed on English segmental and suprasegmental PA, alongside vocabulary, at a single time point. The results showed that both segmental PA (elision and segmenting nonwords) and suprasegmental PA (aural suffix judgment and written suffix judgment) were significantly correlated with English real word and pseudoword reading of both NE and NC children, and NC adults, but not NE adults. Moreover, for NE and NC children, segmental PA correlated stronger with real word reading than suprasegmental PA after controlling for vocabulary. Among NC adults, both segmental and suprasegmental PA significantly contributed to real word reading. For pseudoword reading, after controlling for vocabulary, segmental PA had a stronger correlation among NC children and adults, while suprasegmental PA was more influential for NE children. This research gives insights into factors influencing NC speakers' English word reading ability, bearing essential implications for enhancing second language literacy in learners from a logographic background.